FAKTOR-FAKTOR YANG MEMPENGARUHI INFERTILITAS PRIMER PADA MASA REPRODUKSI DI RSUD GUNUNG TUA - Denni Hermartin; Nazri Adlani Siregar (Jurnal Sains Riset, 2021)
Infertility is a condition where a married couple has not been able to have children even though they have had regular sexual relations within one year without using any type of contraception. There are several factors that can cause infertility such as sex, age, nutritional status and lifestyle factors. The purpose of this study is to identify the factors that influence the incidence of primary infertility during reproduction in RSUD Gunungtua. This research uses analytic research design with cross sectional appr`oach, this method is carried out with the aim to find out the factors that influence infertility in Gunung Tua Hospital. The sampling technique in this study is the total sampling technique where the number of samples is equal to the population. Research shows that infertility is caused (55.6%) by sex, (61.1%) by age, (38.9%) by nutritional status factors, (61.1%) by smoking habit factors, (61, 1%) by alcohol consumption factors, and (94.4%) by marijuana consumption factors.Keywords: Infertility, gender, age, nutritional status, lifestyle